Perinatal detection of disomy X cell line by fluorescence in situ hybridization in a pregnancy with 45,X/47,XXX at amniocentesis, cytogenetic discrepancy in various tissues and a favorable outcome - Chih-Ping Chen; Fang-Tzu Wu; Yen-Ting Pan; Peih-Shan Wu; Wen-Lin Chen; Meng-Shan Lee; Wayseen Wang (Elsevier, 2023)
Objective: We present perinatal detection of disomy X cell line by fluorescence in situ hybridization (FISH) in a pregnancy with 45,X/47,XXX at amniocentesis, cytogenetic discrepancy in various tissues and a favorable outcome. Case report: A 34-year-old, gravida 3, para 1, woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 45,X[22]/47,XXX[10]. Simultaneous array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes revealed the result of arr (X) × 1-2, (1-22) × 2, consistent with 32% mosaicism for monosomy X. She was referred for genetic counseling at 19 weeks of gestation. Prenatal ultrasound findings and parental karyotypes were normal. Repeat amniocentesis at 29 weeks of gestation revealed a karyotype of 45,X[36]/47,XXX[4] (Fig. 1) in cultured amniocytes. Simultaneous molecular analysis on uncultured amniocytes revealed the result of arr (1-22) × 2, Y × 0 by aCGH with no genomic imbalance, and 15% (15/100 cells) mosaicism for disomy X, 61% (61/100 cells) mosaicism for monosomy X and 24% (24/100 cells) mosaicism for triple X by interphase fluorescence in situ hybridization (FISH) analysis. The pregnancy was encouraged to continue and at 37 weeks of gestation, a 2834-g phenotypically normal female baby was delivered. The karyotypes of cord blood, umbilical cord and placenta were 45,X[33]/47,XXX[7], 45,X[30]/47,XXX[10] and 47,XXX[38]/45,X[2], respectively. When follow-up at age three months, the neonate was normal in development. FISH analysis on 99 buccal mucosal cells showed 49% (48/99 cells) mosaicism for monosomy X, 8% (8/99 cells) mosaicism for triple X and 43% (42/99 cells) mosaicism for disomy X (Fig. 2). Peripheral blood had a karyotype of 45,X[38]/47,XXX[2]. When follow-up at age nine months, the neonate was normal in development. FISH analysis on 102 buccal mucosal cells showed 11% (11/102 cells) mosaicism for monosomy X, 12% (12/102 cells) mosaicism for triple X and 77% (79/102 cells) mosaicism for disomy X. Peripheral blood had a karyotype of 45,X[30]/47,XXX[10]. Conclusion: 45,X/47,XXX at amniocentesis may detect disomy X cell line by FISH analysis and can be associated with postnatal progressive decrease of the aneuploid cell lines, increase of the disomy X cell line and a favorable outcome.